A 50 dB high-gain operational amplifier integrated with metal-oxide TFTs. (1st October 2022) - Chen, Jun-Rong; Xu, Wen-Xing; Zuo, Wen-Cai; Mei, Xiang-Lin; Zhou, Lei; Xu, Miao; Wang, Lei; Wu, Wei-Jing; Liu, Yu-Rong; Peng, Jun-Biao
Abstract: This paper presents a 50 dB high-gain operational amplifier (OPAMP), which is fabricated by unipolar n-type indium–zinc–oxide thin-film transistors. Different positive feedback technologies are employed to achieve sufficient voltage gain. The fabricated OPAMP exhibits an open-loop voltage gain ( A v ) of 50 dB over a −3 dB bandwidth of 15 kHz at the supply voltage of 20 V. The measured unity-gain frequency ( f UG ) and the DC power consumption are 500 kHz and 8.07 mW, respectively. In addition, an effective frequency compensation scheme is also introduced and simulated. The simulation results that the proposed OPAMP has a voltage gain of 50 dB with 60° phase margin at 150 kHz unity-gain frequency after compensation.